2018
DOI: 10.13075/ijomeh.1896.01162
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between psychosocial risks and occupational functioning among miners

Abstract: Objectives: This paper presents the results of research on the scale of psychosocial risks among miners. A comparative analysis was made, comparing the research results with the data obtained from workers in the following industries: metal, energy, chemical and construction-along with an indication of the relationship between stressful working conditions and the occupational functioning of the respondents. Material and Methods: The study involved 483 adults employed in mines in Poland. The study on psychosocia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 18 publications
(23 reference statements)
1
19
0
3
Order By: Relevance
“…Ergonomic risks relate to the tasks performed by the worker and can result in damage to sensitive parts of the musculoskeletal system, such as injuries and improper postures [44]. Psychosocial risks include anxiety and stress disorders, which contribute to an insufficient work environment, such as workplace violence [45,46]. Machines cause mechanical injuries, resulting in particle projection and other injuries [47,48].…”
Section: Introductionmentioning
confidence: 99%
“…Ergonomic risks relate to the tasks performed by the worker and can result in damage to sensitive parts of the musculoskeletal system, such as injuries and improper postures [44]. Psychosocial risks include anxiety and stress disorders, which contribute to an insufficient work environment, such as workplace violence [45,46]. Machines cause mechanical injuries, resulting in particle projection and other injuries [47,48].…”
Section: Introductionmentioning
confidence: 99%
“…About the Psychosocial problems & health related factors theme, the studies researched on psychosocial risks, interpersonal relations, OH/drug/tobacco consumption and other variables. For example, Amponsah et al 55 ) and Mościcka et al 76 ) inquired on psychosocial risks. The first one related to the physical and psychosocial risks with the worker’s safety experience.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, they used COPSOQ short version along with physical hazards scale that included following variables: mine gas, fires, excessive noise, heat stress, poor visuality and dusty conditions. Then, the study of Mościcka et al 76 ) compared the level of psychosocial risks among industrial workers (one of these were the miners). They defined psychosocial risks supported by European Agency for Safety and Health at Work (EU-OSHA), and used the PRS scale to assess it.…”
Section: Resultsmentioning
confidence: 99%
“…Low job satisfaction is considered an emotional response to job strain. [ 35 ] Being part of a workplace provides workers with good access to social support, which may play an important role in promoting health. [ 30 ] As previous studies have suggested, efforts should be made to improve conditions in both work-related and outside-work areas.…”
Section: Discussionmentioning
confidence: 99%